THE ROLE OF SOCIAL INTERACTION IN SHAPING LANGUAGE SKILLS DURING EARLY CHILDHOOD - Samongilailai, Heltri Firdayati; Damanik, Bernieke Anggita Ristia (Sindoro: Cendikia Pendidikan, 2025)
This study explores the role of social interaction in the development of language skills during early childhood, a critical period for cognitive and linguistic growth. Language acquisition is not merely a cognitive process but also a social one, deeply influenced by interactions with caregivers, peers, and the surrounding environment. This research investigates how varying types and frequencies of social interactions, such as verbal exchanges, storytelling, and collaborative play, contribute to the emergence of vocabulary, syntax, and pragmatic communication. A mixed-methods approach is employed, combining observational studies and parental interviews to understand the dynamics of interaction and language development. Preliminary findings suggest that enriched social environments, characterized by responsive and meaningful interactions, significantly enhance children's linguistic abilities. This research underscores the importance of fostering supportive social contexts to optimize language learning during early childhood.